DEVELOPING STUDENTS SPEAKING SKILL TROUGH GUESSING GAMES - Sukerni, Ida Ayu Kade; Purnami, Ida Ayu Oka (Yavana Bhasha : Journal of English Language Education, 2019)
This study aims at describing how the students can improve their speaking skill and that also part of the teachers’ job. A teacher is expected to have right teaching techniques to provide students with appropriate teaching materials and to create a positive classroom environment. The data of this study were collected through observations, planning, action, and reflection, some of the researchers were conducted in two cycles. The data were obtained by interviewing the English teachers and students. The result of this study showed that the speaking skill can improved through guessing games. These were confirmed by the data on the finding and discussion in the researchers’ article